Trochanteric stabilizing plate in the treatment of trochanteric fractures: a scoping review. (29th October 2021) - Alm, Carl Erik; Gjertsen, Jan-Erik; Basso, Trude; Matre, Kjell; Rörhl, Stephan; Madsen, Jan Erik; Frihagen, Frede
Abstract : Background and purpose — The trochanteric stabilizing plate (TSP) may be used as an adjunct to a sliding hip screw (SHS) in the treatment of trochanteric fractures to increase construct stability. We performed a scoping review of the literature to clarify when and how the TSP may be useful. Methods — A systematic search was performed in 5 databases and followed by a backwards-and-forwards citation search of the identified papers. 24 studies were included. Results — 6 biomechanical studies and 18 clinical studies were included in the review. The studies presented mainly low-level evidence. All studies were on unstable trochanteric fractures or fracture models. Due to the heterogeneity of methods and reporting, we were not able to perform a meta-analysis. In the biomechanical trials, the TSP appeared to increase stability compared with SHS alone, up to a level comparable with intramedullary nails (IMNs). We identified 1, 091 clinical cases in the literature where a TSP had been used. There were 82 (8%) reoperations. The rate of complications and reoperations for SHS plus TSP was similar to previous reports on SHS alone and IMN. It was not possible to conclude whether the TSP gave better clinical results, when compared with either SHS alone or with IMN. Interpretation — The heterogeneity of methods and reporting precluded any clear recommendations on when to use the TSP, or if it should be used at all.